Minat Siswa dalam Pembelajaran Penjas pada Masa Pandemi Covid-19 di SMPN 1 Telukjambe Barat Karawang - Yusril Arfah Setiawan; Abduloh Abduloh; H. Nana Suryana Nasution (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to determine student interest in learning physical education during the COVID-19 pandemic at SMPN 1 Telukjambe Barat Karawang. The research method uses a survey method with a questionnaire or questionnaire in the google form. Based on the results of the study, it can be concluded that students' interest in learning physical education during the covid-19 pandemic at SMPN 1 Telukjambe Barat Karawang was in the "very high" category of 7.33%, "high" category of 20.67%, category “medium” was 43.33%, “low” category was 21.33%, and “very low” was 7.33%. ). Based on the average value (mean), which is 126.18 students' interest in learning physical education during the covid-19 pandemic at SMPN 1 Telukjambe Barat Karawang, it is in the good "moderate" category with an average (mean) score of 126.18